Toxoplasma gondii among captive wild mammals in zoos in Brazil and Cuba: seroprevalence and associated risk factors - Villar-echarte, Ginette; Arruda, Igor Falco; Barbosa, Alynne Da Silva; Guzmán, Raiden Grandía; Augusto, Anderson Mendes; Troccoli, Fernando; Segón, Alejandro Manuel Rodríguez; Santos, Ana Letícia Carvalho; Zanotto, Paula Ferraz De Camargo [UNESP]; Gava, Mariana Zanchetta E [UNESP]; Langoni, Hélio [UNESP]; Amendoeira, Maria Regina Reis (Colégio Brasileiro de Parasitologia Veterinária, 2021)
Toxoplasma gondii is a zoonotic parasite of worldwide distribution that can infect several species of homeothermic animals. Few studies have evaluated the exposure of captive wild animals to T. gondii. This study involved a serological survey of anti-T. gondii antibodies in mammals kept in Cuba’s National Zoo (PZN) and in the Rio de Janeiro Zoo (RIOZOO) in Brazil. The study consisted of a total of 231 serum samples from mammals, 108 from PZN and 123 from RIOZOO. All the samples were subjected to IgG anti-T. gondii testing by means of the inhibition ELISA method and the modified agglutination test, respectively. T. gondii antibodies were detected in 85.2% samples from PZN and 32.5% samples from RIOZOO. At the PZN, Perissodactyla (92.3%) was the order with the highest serological prevalence rate, whereas at the RIOZOO, the order Primates (46.7%) stood out (p<0.05). In addition to this association, the origin of the PZN animals was also associated with T. gondii infection. This finding demonstrates the need for constant veterinary monitoring of captive wild mammals in order to link the serological diagnosis with clinical alterations indicative of toxoplasmosis.

Toxoplasma gondii é um parasito zoonótico de distribuição mundial que pode infectar várias espécies de animais homeotérmicos. Poucos estudos avaliaram a exposição de animais silvestres em cativeiro ao T. gondii. Este estudo envolveu uma pesquisa sorológica de anticorpos anti-T. gondii em mamíferos mantidos no Zoológico Nacional de Cuba (PZN) e no Zoológico do Rio de Janeiro (RIOZOO) no Brasil. O estudo consistiu em um total de 231 amostras de soro de mamíferos, sendo 108 do PZN e 123 do RIOZOO. Todas as amostras foram submetidas à pesquisa de IgG anti-T. gondii pelos métodos de ELISA de inibição (PZN) e teste de aglutinação modificado (RIOZOO). Anticorpos de T. gondii foram detectados em 85,2% das amostras do PZN e 32,5% das amostras do RIOZOO. No PZN, Perissodactyla (92,3%) foi a ordem com maior taxa de prevalência sorológica, enquanto no RIOZOO a ordem Primatas (46,7%) se destacou (p <0,05). Além dessa associação, a origem dos animais PZN também foi associada à infecção por T. gondii. Esse achado demonstra a necessidade de monitoramento veterinário constante de mamíferos silvestres em cativeiro, a fim de vincular o diagnóstico sorológico a alterações clínicas indicativas de toxoplasmose.
Toxoplasma gondii entre mamíferos silvestres cativos em zoológicos no Brasil e em Cuba: soroprevalência e fatores de risco associados
Keywords: toxoplasmosis; serology; zoo animals; toxoplasmose; sorologia; animais de zoológicos